2021
DOI: 10.7554/elife.74047
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Xrp1 is required for PERK-mediated antioxidant gene induction in Drosophila

Abstract: PERK is an endoplasmic reticulum (ER) transmembrane sensor that phosphorylates eIF2a to initiate the Unfolded Protein Response (UPR). eIF2a phosphorylation promotes stress-responsive gene expression most notably through the transcription factor ATF4 that contains a regulatory 5' leader. Possible PERK effectors other than ATF4 remain poorly understood. Here, we report that the bZIP transcription factor Xrp1 is required for ATF4-independent PERK signaling. Cell type-specific gene expression profiling in Drosophi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 87 publications
4
33
0
Order By: Relevance
“…Our motif analysis revealed an enrichment for Xrp1/Irbp18 heterodimer binding site motifs in promoters of glutathione metabolism transcripts, suggesting a potential alternate regulator of this pathway during aging. Xrp1 has recently been shown to induce glutathione-S-transferases as part of the PERK-mediated unfolded protein response [41], corroborating our motif analysis results.…”
Section: Discussionsupporting
confidence: 88%
“…Our motif analysis revealed an enrichment for Xrp1/Irbp18 heterodimer binding site motifs in promoters of glutathione metabolism transcripts, suggesting a potential alternate regulator of this pathway during aging. Xrp1 has recently been shown to induce glutathione-S-transferases as part of the PERK-mediated unfolded protein response [41], corroborating our motif analysis results.…”
Section: Discussionsupporting
confidence: 88%
“…Knockdown of Xrp1 or Irbp18 rescues proteotoxic stress in RpS3/+ cells, suggesting that this feed-forward loop is essential for build-up of proteotoxic stress and to reduce the competitiveness of Rp/+ cells. We note that during the revision of this manuscript two other independent studies have reported relevant and complementary findings [ 46 , 47 ]. Nrf2 is also activated by proteotoxic stress and contributes to this feedback loop, either independently of p-eIF2α (as illustrated in Fig 6G ), or downstream of p-eIF2α.…”
Section: Discussionmentioning
confidence: 65%
“…Consistently, we found that overexpression of PERK leads to upregulation of Xrp1 expression ( S6 Fig ). In addition, recent studies have shown that overexpression of PERK or ATF4 upregulates Xrp1 [ 32 , 34 ]. These observations suggest that Xrp1 acts both upstream and downstream of the PERK-eIF2α axis in a positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%